MEMAHAMI KAIDAH AL KHARĀJ BI AL DHOMĀN TERHADAP FLUKTUASI HARGA ALAT PELINDUNG DIRI (APD) PADA MASA PANDEMI COVID-19 - Farida, Ulfa Jamilatul (Ekonomi Syariah STAI Sangatta Kutai Timur, 2022)
This paper discusses price fluctuations for personal protective equipment (PPE) during the Covid-19 pandemic in terms of Islamic economic law in the principles of al kharāj bi al dhomān. This issue is very interesting for two reasons: the massive phenomenon of PPE hoarding during the pandemic and the need for an understanding of sharia economic law to be empowered to understand the risks associated with fluctuations in PPE prices during the pandemic. This paper is a qualitative research with a sociological juridical approach. In the perspective of sharia economic law, especially in the context of the rules of al kharāj bi al dhomān, ideally PPE producers or resellers should dare to take risks due to pandemic conditions and not, so they carry out hoarding under the pretext of waiting for prices to stabilize or worry that they will not be able to buy more products to be resold. These conditions caused the price of PPE to increase many times. Within the framework of the rules of al kharāj bi al dhomān, producers or resellers must be able to make mitigations to bear the risk of profit and risk of loss. In terms of consumer protection, the government's role is very important. Mitigation measures can be taken with government regulations to standardize prices, market operations, and strict regulations that will catch violators during a pandemic.